Observing the messier objects with a small telescope in the footsteps of a great observer - Pugh, Philip (Patrick Moore's Practical Astronomy Series, 2012)
Observing the Messier Objects with a Small Telescope lets the reader follow in Charles Messier's footsteps by observing the Messier objects more or less as the great man saw them himself! This book contains descriptions and photographs of  his 110 cataloged objects, with instructions on how to find them without a computerized telescope or even setting circles. Messier's telescope (thought to be a 4-inch) was, by today's amateur standards, small. It also had rather poor optics by modern standards. The visual appearance of a Messier object is often very different from what can be imaged with the same telescope, and this book shows what you can see with a small telescope or even binoculars!